Failure mechanism and control of the coal bursts triggered by mining-induced seismicity: a case study - Cao, Jinrong; Dou, Linming; Konietzky, Heinz; Zhou, Kunyou; Zhang, Min (Environmental earth sciences, 2023)
Mining-induced seismicity-triggered coal bursts (MISTCB) have become a major impediment to the safety of underground coal mining. Based on a severe MISTCB that occurred in China, this paper investigates the mechanism and control strategy of the MISTCB. A large-scale numerical model was built using the Universal Distinct Element Code (UDEC). Crack development and stress evolution of the MISTCB is analysed. In addition, the effect of mining-induced seismicity amplitude on the MISTCB is discussed. It is shown that severe dynamic failure occurred at both sidewalls and the floor of the roadway, including tensile failure near the roadway surface and shear failure in regions further away from the surface. After the coal burst, the distances between the two sidewalls and between roof and floor are 2.7 m and 3.1 m (4 and 5 m before the MISTCB). The maximum ejection velocity is up to 27.2 m/s. Mining-induced seismicity plays a key role for a MISTCB, whereas the amplitude (energy) is decisive for the strength of the dynamic failure. Increasing amplitude means increasing dynamic stresses, increasing ejection velocities of fragments and increasing deformations. However, the changes in dynamic stresses and deformations incl. damage patterns in the plastic, elasto-plastic and elastic zones are different. A zonation failure mechanism is proposed for the MISTCB. The obtained numerical results are in good agreement with the field measurements. The results are helpful for deeper understanding of the mechanism and to control the MISTCB.